Eye movements during path integration - Churan, Jan; Hopffgarten, Anna; Bremmer, Frank (Physiological reports, 2018)
Self‐motion induces spontaneous eye movements which serve the purpose of stabilizing the visual image on the retina. Previous studies have mainly focused on their reflexive nature and how the perceptual system disentangles visual flow components caused by eye movements and self‐motion. Here, we investigated the role of eye movements in distance reproduction (path integration). We used bimodal (visual‐auditory)‐simulated self‐motion: visual optic flow was paired with an auditory stimulus whose frequency was scaled with simulated speed. The task of the subjects in each trial was, first, to observe the simulated self‐motion over a certain distance (Encoding phase) and, second, to actively reproduce the observed distance using only visual, only auditory, or bimodal feedback (Reproduction phase). We found that eye positions and eye speeds were strongly correlated between the Encoding and the Reproduction phases. This was the case even when reproduction relied solely on auditory information and thus no visual stimulus was presented. We believe that these correlations are indicative of a contribution of eye movements to path integration. We investigated the role of eye movements in distance reproduction (path integration). We used bimodal (visual‐auditory)‐simulated self‐motion in which visual optic flow was paired with an auditory stimulus whose frequency was scaled with simulated speed. We found that eye positions and eye speeds were strongly correlated between the encoding of distance and the reproduction even when reproduction relied solely on auditory information and thus no visual stimulus was presented.